The Socialization Model of National Character Education for Students in Elementary School Through Comic - Astuti, Tri Marhaeni Puji; Kismini, Elly; Prasetyo, Kuncoro Bayu (KOMUNITAS: International Journal of Indonesian Society and Culture, 2014)
Realizing the character building on students is a national education goal. The character education is very important for the students. Therefore, the socialization and enculturation of national character education in schools by using an effective and efficient method are needed. This study aims to understand the process of socialization of character education in elementary school, to find the effective way of socialization models of national character education for students in elementary school through comics, and to determine the impact of socialization models of national character education for students in elementary school through the comic for the character building of students. This research was conducted using qualitative methods (Research & Development). The data collection techniques used were interviews, observation and documentation. The results show that the socialization of the nation’s character education in primary schools is done in several ways; integrated with in the curriculum through the school management, and through extracurricular programs. Those ways do not seem to produce maximum results. Socialization model of the national character of education in the elementary schools through the comic is more effective to apply, because students are more interested in the visualization of interesting and familiar images.Menyadari pembangunan karakter siswa adalah tujuan pendidikan nasional. Pendidikan karakter sangat penting bagi para siswa. Oleh karena itu, sosialisasi dan enkulturasi pendidikan karakter bangsa di sekolah-sekolah dengan menggunakan metode yang efektif dan efisien diperlukan. Penelitian ini bertujuan untuk memahami proses sosialisasi pendidikan karakter di sekolah dasar, untuk menemukan cara yang efektif untuk model sosialisasi pendidikan karakter bangsa bagi siswa di sekolah dasar melalui komik, dan untuk menentukan dampak dari model sosialisasi pendidikan karakter bangsa bagi siswa di sekolah dasar melalui komik untuk membangun karakter siswa. Penelitian ini dilakukan dengan menggunakan metode kualitatif (Research & Development). Teknik pengumpulan data yang digunakan adalah wawancara, observasi dan dokumentasi. Hasil menunjukkan bahwa sosialisasi pendidikan karakter bangsa di sekolah dasar ini dilakukan dengan beberapa cara, terintegrasi dengan subjek termasuk, melalui manajemen sekolah, dan melalui program ekstrakurikuler. Mereka cara tampaknya tidak menghasilkan hasil yang maksimal. Model Sosialisasi karakter nasional pendidikan di sekolah dasar melalui komik lebih efektif untuk diterapkan, karena siswa lebih tertarik pada visualisasi gambar yang menarik dan akrab.